Highly stable In-SBA-15 catalyst for vapor phase Beckmann rearrangement reaction - Kumar, Rawesh; Shah, Sneha; Bahadur, Jitendra; Melnichenko, Yuri B.; Sen, Debasis; Mazumder, S.; Vinod, Chathakudath P.; Chowdhury, Biswajit (Microporous and Mesoporous Materials, 2016)
The Indium doped SBA-15 material was prepared by sol-gel method and tested for vapor phase Beckman rearrangement reaction. Among three indium loading, In/Si ratio of 2/100 was found as an optimum composition in terms of caprolactam selectivity (100%) and cyclohexanone oxime conversion (100%). The catalysts were characterized by N-2 adsorption, small-angle X-rays/neutron scattering (SAXS/SANS), XRD, FESEM, HRTEM, EDX, UV, FTIR and NH3-TPD techniques. In-situ SANS experiment was performed on the adsorption of CO2 to detect the micropores in the mesopore wall. All catalysts samples have highly ordered hexagonal structure with well dispersed indium in the silica matrix. The fine tuning of weak and strong acid sites were found in indium doped SBA-15 (In/Si = 2/100) catalyst. The same catalyst showed optimum catalytic performance, high space time yield 114.4 mol/h/g(cat) and high stability till 6 h of reaction without deactivation. The micro-kinetic analysis showed that there were no external and internal diffusion limitations in the SBA-15 catalyst. The reaction mechanism of Beckmann rearrangement over In-SBA-15 has been elucidated. (C) 2016 Elsevier Inc. All rights reserved.
Keywords: e-Caprolactam; In-situ SANS; indium; SAXS; SBA-15

Highly stable COF-supported Co/Co(OH)(2) nanoparticles heterogeneous catalyst for reduction of nitrile/nitro compounds under mild conditions - Mullangi, Dinesh; Chakraborty, Debanjan; Pradeep, Anu; Koshti, Vijay; Vinod, Chathakudath P.; Panja, Soumendranath; Nair, Sunil; Vaidhyanathan, Ramanathan (Small, 2018)
Ordered nanoporosity in covalent organic framework (COF) offers excellent opportunity for property development. Loading nanoparticles (nPs) onto them is one approach to introducing tailor-made properties into a COF. Here, a COF-Co/Co(OH)(2) composite containing about 16 wt% of <6 nm sized Co/Co(OH)(2) nPs is prepared on a N-rich COF support that catalyzes the release of theoretical equivalence of H-2 from readily available, safe, and cheap NaBH4. Furthermore, the released H-2 is utilized for the hydrogenation of nitrile and nitro compounds to amines under ambient conditions in a facile one-pot reaction. The COF "by choice" is built from "methoxy" functionalized dialdehydes which is crucial in enabling the complete retention of the COF structure under the conditions of the catalysis, where the regular Schiff bonds would have hydrolyzed. The N-rich binding pockets in the COF ensure strong nP-COF interactions, which provides stability and enables catalyst recycling. Modeling studies reveal the crucial role played by the COF in exposing the active facets and thereby in controlling the activation of the reducing agent. Additionally, via density functional theory, we provide a rational explanation for how these COFs can stabilize nanoparticles which grow beyond the limiting pore size of the COF and yet result in a truly stable heterogeneous catalyst - a ubiquitous observation. The study underscores the versatility of COF as a heterogeneous support for developing cheap and highly active nonnoble metal catalysts.

Hydrogenation of glucose to sorbitol by using nickel hydroxyapatite catalyst - Kamble, Paresh A.; Vinod, Chathakudath P.; Rathod, Virendra K.; Lakshmi Kantam, Mannepalli (Chemcatchem, 2024)
A series of nickel hydroxyapatite catalysts were synthesized by the co-precipitation method followed by calcination and reduction. These catalysts were employed for the aqueous phase hydrogenation of glucose to sorbitol. The Ni-HAP catalyst with comparatively high surface area and acid-base strength gave high sorbitol selectivity in 1 h. Ni-HAP-4 catalyst with moderate Ni (3.5 wt. %) content having smaller and highly dispersed nickel particles gives an excellent yield of sorbitol, 97 % in 1 h. The Ni-HAP-4 catalyst works well with other polar protic solvents. Different characterization techniques like XRD, TEM, SEM-EDS, BET, NH3-TPD, and CO2-TPD were employed to analyze the Ni-HAP-4 catalyst. A facile hydrogenation of glucose to sorbitol has been reported with Ni-HAP catalyst using water as a solvent. The excellent yield of sorbitol, 97 % in 1 h is possible due to the high surface area and high acid-base strength of the Ni-HAP-4 catalyst. image
Keywords: glucose; Hydrogenation; Hydroxyapatite (HAP); Nickel; Sorbitol